Acetone and Isopropyl Alcohol Vapor Sensing Properties of NiO Films Under Varying Bias Voltages at Room Temperature - Sahin, Ayse Nur; Altindal, Ahmet; Guven Ozdemir, Zeynep (WILEY-V C H VERLAG GMBH, 2025)
This study aims to evaluate the sensing performance of nickel oxide (NiO) particles in detecting acetone and isopropyl alcohol (IPA) vapors. NiO particles are synthesized using the hydrothermal method, and their optical properties are characterized using a UV-vis spectrophotometer, with the bandgap calculated to be 3.3 eV. The sensing capabilities of the NiO particles for acetone and IPA vapors are tested under ambient conditions, with vapor concentrations varying between 3 and 21%, and bias voltages of 0, 0.5, 0.7, and 0.9 V. The results show that the response of the NiO particles improves as vapor concentrations increase. The best sensing performance is observed for acetone vapor without the application of any bias voltage. Moreover, the sensor's sensitivity to acetone vapor significantly increases at higher vapor concentrations in the absence of bias voltage. These findings suggest that NiO particles can be a promising alternative for acetone vapor sensing without the need for an applied voltage.
Keywords: bias voltages; NiO films; optic; volatile organic compounds sensing; NICKEL-OXIDE NANOSTRUCTURES; GAS; NANOPARTICLES; FABRICATION; SIZE; Materials Science; Physics